2010
DOI: 10.1109/tasc.2009.2039746
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Transport-Current Losses in ${\rm MgB}_{2}$ Superconducting Wire on Temperature and Frequency

Abstract: AC losses of a monofilamentary MgB2 wire in a selffield are experimentally evaluated at several temperatures and frequencies. The alternating transport currents are applied to the straight sample wire, and the AC losses are observed electrically with a lock-in amplifier. The temperature of the sample wire was adjusted by a conduction cooling with gaseous helium, and the stability was below ±0.1 K near a fixed temperature. The temperature dependence of the transport-current losses was roughly expained with a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Since both the windings for rotor and stator in the fully superconducting motor for liquid hydrogen pump proposed by our group are located inside the slots of iron cores, the winding in one of the core slots under consideration is mainly exposed to a self-field due to the magnetic flux passing through the parts of iron teethes generated by all of the remaining windings in the other slots [1]. Thus, the AC losses in an MgB 2 sample wire carrying an alternating transport current have been evaluated at several temperatures and frequencies systematically [2,3]. The MgB 2 wire had a round cross section and a three-layer structure of a central superconductor filament surrounded by niobium and copper sheaths as shown in Fig.…”
Section: Proposal Of New Architecture Of Sc Wirementioning
confidence: 99%
See 1 more Smart Citation
“…Since both the windings for rotor and stator in the fully superconducting motor for liquid hydrogen pump proposed by our group are located inside the slots of iron cores, the winding in one of the core slots under consideration is mainly exposed to a self-field due to the magnetic flux passing through the parts of iron teethes generated by all of the remaining windings in the other slots [1]. Thus, the AC losses in an MgB 2 sample wire carrying an alternating transport current have been evaluated at several temperatures and frequencies systematically [2,3]. The MgB 2 wire had a round cross section and a three-layer structure of a central superconductor filament surrounded by niobium and copper sheaths as shown in Fig.…”
Section: Proposal Of New Architecture Of Sc Wirementioning
confidence: 99%
“…The AC losses in a MgB 2 monofilamentary wire carrying alternating transport currents have been evaluated at several temperatures and frequencies so far [2]. By combining the numerical calculations with a finite difference method and the theoretical analysis for an eddy-current loss in a metal sheath with low resistivity, the experimental results have been reproduced very well and the physical mechanism of AC losses in the MgB 2 monofilamentary wire has been revealed clearly [3].…”
Section: Introductionmentioning
confidence: 97%
“…Multifilamentary MgB2 wires have been manufactured to reduce AC losses [9], [10]. Kajikawa et al [11] have studied transport current AC loss of a single core MgB2 wire with copper sheath, they found the dependence between AC loss and frequency might be caused by the copper sheath. Hong et al [12] found that AC loss in multifilamentary MgB2 wire was lower than monofilamentary wire with the same current.…”
Section: Introductionmentioning
confidence: 99%